Paradigms and policies: The state of economics in the german-speaking countries - Christian Grimm; Stephan Pühringer; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2018)
This paper studies the research interests, paradigmatic orientation and political orientation of about 700 full professors of economics at universities located in German-speaking countries. In doing so, we captured biographical and institutional information on these professorships by collecting data from personal and professional websites as well as publicly available CVs to derive indicators on the research orientation, the paradigmatic stance and the political involvement. The main contribution of this paper, hence, is empirical in nature. It documents the fairly homogenous paradigmatic stance of German-speaking academic economics, as criticized in recent debates on pluralism in economics, but also identifies venues of change within the existing paradigmatic setup. Furthermore, we show that a big share of German economists, active in economic policy advice bodies have institutional connections to the ordoliberal research program. This politico-ideological conjunction thus provides a possible explanation for the "German special path" in economic policy after the financial crisis.
Keywords: A11; A14; B5; 330; socio-economics; economic sociology; institutions; economic thought; Germany